Positive and negative religious coping as predictors of distress among minority older adults. (30th October 2018) - O'Brien, Brittany; Shrestha, Srijana; Stanley, Melinda A.; Pargament, Kenneth I.; Cummings, Jeremy; Kunik, Mark E.; Fletcher, Terri L.; Cortes, Jose; Ramsey, David; Amspoker, Amber B.
Abstract : Objectives: The study replicated and extended previous findings by investigating relationships between positive and negative religious coping and psychological distress in minority older adults. Methods: Older adults were evaluated during screening and baseline procedures of a psychotherapy clinical trial for late‐life worry and anxiety. Participants were age 50 years or older and recruited from low‐income and predominantly minority neighborhoods. Participants screening positive for worry (PSWQ‐A ≥ 23) with no significant cognitive impairment (Six‐Item Screener for cognitive impairment ≤2) completed a diagnostic interview and baseline assessments. Positive and negative religious coping were assessed with the positive and negative coping subscales of the Brief Religious Coping scale. Psychological distress was assessed with measures of depression, anxiety, and worry. A set of multiple linear regression models were used to evaluate the relationship between religious coping and each measure of psychological distress. Results: Negative religious coping was associated with greater anxiety, worry, and depression. Positive and negative religious coping interacted such that positive religious coping buffered the effects of negative religious coping on anxiety and depression. Significant main effects and interactions remained after controlling for age, gender, race, years of education, and study. Conclusions: The findings of this study are consistent with prior work showing that negative religious coping is associated with greater psychological distress. This study replicates previous findings that positive religious coping may buffer the harmful effects of negative religious coping and extends understandings of the specific psychological impacts that positive and negative religious coping may have on older, minority adults.